Pelatihan Budikdamber bagi Kelompok PKK Desa Dukuhmojo Jombang Sebagai Upaya Meningkatkan Produktivitas Pekarangan Sempit - Yuliana, Anggi Indah; Satiti, Wisnu Siwi; Fauziah, Annisa’ Khurun Ain; Syatirrodhiatin, Putri Alfi; Aji, Rois Sekti; Chasib, Nur (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Family Empowerment and Welfare (PKK) is a community organization in Indonesia that operates to empower women, especially housewives. The main objective of the PKK program is to improve the welfare of families and communities, especially through empowering women. Therefore, this community service activity focuses on empowering women in the form of training on the fish farming system in buckets (budidaya ikan dalam ember). Budidaya ikan dalam ember (budikdamber) is an aquaponics (fish and vegetable polyculture) which is carried out by utilizing a narrow area of the house yard to cultivate fish and vegetables in containers. Making a budikdamber system does not require expensive costs because it can use used household tools or items. Apart from that, the budikdamber system does not require water and large areas of land. Therefore, this system is suitable for application in narrow yard areas. This service activity was carried out by adopting the Participatory Action Research (PAR) method. The partners or targets of this community service activity are PKK women from Dukuhmojo village, Mojoagung subdistrict, Jombang regency. The results of the training activities show that through these training activities partners gain knowledge and understanding of the budikdamber system. After attending the training, the partners stated that the budikdamber system could make home gardens more productive. Apart from that, training activities also motivate participants to implement the budikdamber system in their respective home environments.